2013
DOI: 10.1021/jp310740h
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Understanding of Enhanced Photoelectrochemical Catalytic Activity of Sn-Doped Hematite: Anisotropic Catalysis and Effects of Morin Transition and Sn Doping

Abstract: To investigate the influence of the Morin transition on the photoelectrochemical (PEC) activity of hematite, electronic properties in different magnetic phases were studied on the basis of the first-principles calculations within the GGA+U approximation. The results show that the effective electron mass in the (0001) plane changes remarkably due to the spin−flop transition, while the effective electron masses in other Miller planes are not sensitive to the spin orientation around irons. The electronic structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 44 publications
4
41
1
Order By: Relevance
“…Moreover, it has been shown theoretically that Sn doping can lead to decreased effective masses of the charge carriers and hence to higher charge carrier mobilities. [33] Since the unfavorable charge transport properties of hematite are considered to be a main reason for high electron-hole recombination rates, an enhancement of the conductivity via doping is a crucial requirement to obtain high photocurrents with hematite photoelectrodes. [34] In the next step we investigated the possible effects of Sn doping on the electrostatic potential within hematite, in order to clarify whether Sn doping might lead to a favorable downward band bending that drives electrons from the hematite bulk to the FTO substrate and holes in the opposite direction.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been shown theoretically that Sn doping can lead to decreased effective masses of the charge carriers and hence to higher charge carrier mobilities. [33] Since the unfavorable charge transport properties of hematite are considered to be a main reason for high electron-hole recombination rates, an enhancement of the conductivity via doping is a crucial requirement to obtain high photocurrents with hematite photoelectrodes. [34] In the next step we investigated the possible effects of Sn doping on the electrostatic potential within hematite, in order to clarify whether Sn doping might lead to a favorable downward band bending that drives electrons from the hematite bulk to the FTO substrate and holes in the opposite direction.…”
Section: Resultsmentioning
confidence: 99%
“…In these previous reports, the role of Sn doping on the electronic and optical properties of hematite nanostructure has been extensively studied. Based on the first‐principles calculations within the GGA+ U approximation, Sn doping can narrow the bandgap of hematite . The incorporated Sn dopants also lead to a lattice distortion of hematite, which enhancing its optical absorption coefficient .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a more electrically conductive semiconductor electrode can reduce the energy loss due to the internal resistance of electrode and the contact resistance at the semiconductor/back contact interface . The electronic structure calculation based on the first‐principles calculations within the GGA+ U approximation showed that Sn‐doped hematite exhibits an improved electrical conductivity due to the reduction of electron effective mass at the conduction band minimum . Heavily Sn‐doped hematite also appears to have a reduced bandgap, which leads to enhanced utilization ratio of solar energy and the expansion of optical absorption scope …”
Section: The Effect Of Sn Doping On the Optical And Electronic Propermentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray diffraction clearly indicates that Sn is present within the crystallized Fe 2 O 3, whereas HRTEM, EDS, and XPS indicatet he formationo faSnO 2 overlayer.E lectronic structure calculations have attributed the effect of Sn doping to be predominantly an increasei nc arrier concentration [30] or even ar eduction in the electron effective masses. [31] Although we have no evidence of mobility improvement,e stimation using Mott-Schottky analysisi ndicates ah igher carrier density for the ALD-treated samples highlighting the doping effect of Sn (relative to untreated Fe 2 O 3 ). However,s uch an increasei nd oping density should reduce the space-charge width, which determines the collection length of the minority carriers being driven towardst he electrolyte interface.…”
Section: Resultsmentioning
confidence: 99%